Does Happiness Depend On Socioeconomic Conditions? Knowledge Gained From Indonesia - Anwar, Syaiful; Yulia Sari, Anita; Bachtiar, Nasri; Fahmy, Rahmi (Green Publisher Indonesia, 2023)
The objective of this study is to identify and examine the socioeconomic variables that affect happiness in Indonesia. Secondary data from the Indonesia Family Life Survey (IFLS) batch 5 survey, which included 16,698 respondents, was the source of the information used in this study. The probit model is used in the data analysis technique using a multilevel category as the dependent variable. According to the study's findings, age, gender, social capital, including religious observance and a sense of security, variable consumer spending, and willingness to help variables have no bearing on the likelihood of happiness in Indonesia. Neither do income level, health, education, or age. Income, education, health, and social capital levels